Imaging methods in monitoring gout – a pictorial essay - Korzeń Maria; Nowakowska-Płaza Anna; Leszkiewicz Marek; Sudoł-Szopińska Iwona (Journal of Ultrasonography)
We present a pictorial essay based on the case of a 52-year-old man suffering from chronic gout, who was followed up for seven years. During this period of time, radiographs, ultrasonography, and dualenergy computed tomography were performed several times, revealing severe progression of gout. This was most likely due to the lack of patient compliance. Inflammatory and destructive lesions were observed in the wrists, in the metacarpophalangeal and proximal interphalangeal joints. Ultrasonography showed tenosynovitis, synovitis with small calcifications in the synovial membrane. Radiographs obtained in later stages showed tophi and bone erosions. Dual-energy computed tomography showed deposits of monosodium urate crystals in different locations, which increased in volume over time. This modality can be used to confirm a clinical diagnosis of gout, especially in early stages of the disease, and to follow up the treatment.